Increased prevalence of pfdhfr and pfdhps mutations associated with sulfadoxine–pyrimethamine resistance in Plasmodium falciparum isolates from Jazan Region, Southwestern Saudi Arabia: important implications for malaria treatment policy - Aymen M. Madkhali; Hesham M. Al-Mekhlafi; Wahib M. Atroosh; Ahmad Hassn Ghzwani; Khalid Ammash Zain; Ahmed A. Abdulhaq; Khalid Y. Ghailan; Alkhansa A. Anwar; Zaki M. Eisa (Malaria Journal, 2020)
Abstract Background Despite significant progress in eliminating malaria from the Kingdom of Saudi Arabia, the disease is still endemic in the southwestern region of the country. Artesunate plus sulfadoxine–pyrimethamine (AS + SP) has been used in Saudi Arabia since 2007 as a first-line treatment for uncomplicated Plasmodium falciparum malaria. This study aimed to investigate the prevalence of mutations associated with resistance to artemisinin and sulfadoxine–pyrimethamine (SP) resistance in P. falciparum parasites circulating in Jazan region, southwestern Saudi Arabia. Methods A total of 151 P. falciparum isolates were collected between April 2018 and March 2019 from 12 of the governorates in Jazan region. Genomic DNA was extracted from dried blood spots and amplified using nested PCR. Polymorphisms in the propeller domain of the P. falciparum k13 (pfkelch13) gene and point mutations in the P. falciparum dihydrofolate reductase (pfdhfr) and dihydropteroate synthase (pfdhps) genes were identified by sequencing. Results No mutations in the pfkelch13 propeller domain were found in any of the 151 isolates. However, point mutations in the pfdhfr and pfdhps genes were detected in 90.7% (137/151) of the isolates. The pfdhfr double mutations N51I + S108N (i.e. ACICNI haplotype) and triple mutations N51I + C59R + S108N (i.e. ACIRNI haplotype) were detected in 47% and 37.8% of the isolates, respectively. Moreover, the pfdhps single mutation at codon A437G and double mutations A437G + K540E (i.e. SGEAAI haplotype) were observed in 4.6% and 51.7% of the isolates, respectively. Interestingly, 23.8%, 25.1 and 12.6% of the isolates had quintuple, quadruple and triple mutated combined pfdhfr–pfdhps genotypes, respectively. Furthermore, significant associations were found between the prevalence of mutant haplotypes and the age, gender and nationality of the patients (P < 0.05). Conclusion This study revealed a high prevalence of point mutations in the pfdhfr and pfdhps genes of P. falciparum isolates from Jazan region, with ...